Community Readiness in Utilization of Android Application (mHealth) for Increasing Healthy Family Index - Aliyanto, Warjidin; Suarni, Lisa; Sono, Sono (Jurnal Kesehatan, 2025)
SIPISPeKa G-2 was introduced as an innovative mHealth solution to bridge this gap by enabling real-time communication between families and health workers. This study aims to evaluate the effectiveness of the SIPISPeKa G-2 mHealth application in improving the Healthy Family Index (IKS) in the work area of Kotabumi 2 Health Center, North Lampung. The quasi-experimental pre-test and post-test design was carried out on 150 families who were categorized as unhealthy based on 12 IKS indicators. The study was conducted from February to November, with a trial period of 3 months. Sampling using the Multi-Stage method, the results showed a significant increase in the Healthy Family Index (IKS) from an IKS value of 0.64 to 0.79 (p < 0.05). The most widely accessed services were smoking cessation services (29.01%), National Health Insurance 16.41%), and hypertension (16.03%). However, 16.03% of consultations were deemed irrelevant, indicating the need for further education. This study concluded that the mHealth application can effectively improve family health, with recommendations for optimization and broader implementation.